Pengawasan Otoritas Jasa Keuangan terhadap Praktek Fintech Peer to Peer Lending yang Merugikan Konsumen Jasa Keuangan - Anwar Hafidz Amrullah; Neni Sri Imaniyati (UNISBA Press, 2022)
Abstract. The presence of this globalization has provided the development of the fintech peer to peer lending industry in Indonesia, but problems are found in the peer to peer lending industry in Indonesia, namely the large number of illegal peer to peer lending fintechs that can harm financial consumers. The Financial Services Authority as an independent institution that oversees financial services has the authority to regulation and supervision of fintech peer to peer lending. The purpose of this study is to explain the regulation regarding the supervision of the Financial Services Authority on the practice of fintech peer to peer lending and to explain the implementation of the supervision of the Financial Services Authority against irregularities in the practice of fintech peer to peer lending that harms consumers of financial services in terms of law positive. The research method used is normative juridical because this research is based on the approach of OJK legislation relating to fintech peer to peer lending related to the supervision of the Financial Services Authority on the practice of fintech peer to peer lending that harms consumers of financial services. The regulation regarding OJK supervision of fintech peer to peer lending was first held in 2016 namely POJK No. 77/POJK.01/2016 concerning Technology-Based Lending and Borrowing Services which discusses the implementation of the mechanism for implementing fintech peer to peer lending and only supervises sub-sectorally. , this form of supervision is external supervision. Regarding sanctions in POJK No.77/POJK.01/2016 there is no legal certainty and can lead to disputes in the future, in 2018 OJK issued POJK regulation No.13/POJK.02/2018 concerning Digital Financial Innovation as a form of preventive supervision. The implementation of OJK supervision on irregularities in the practice of fintech peer to peer lending that harms consumers of financial services. The author's suggestion for OJK is to regulate more clearly and specifically regarding the supervision contained in POJK regulation No.77/POJK.01/2016 and for the Investment Alert Task Force to improve the detection system for illegal fintech peer to peer lending and improve the quality in supervision of fintech peer to peer lending illegal. Abstrak. Hadirnya globalisasi ini memberikan perkembangan industri fintech peer to peer lending di Indonesia namun ditemukan permasalahan dalam industri peer to peer lending di Indonesia yaitu banyaknya fintech peer to peer lending illegal yang dapat merugikan konsumen keuangan Otoritas Jasa Keuangan sebagai lembaga independen yang mengawasi jasa keuangan memiliki kewenangan dalam pengaturan dan pengawasan fintech peer to peer lending dalam Tujuan penelitian ini adalah untuk menjelaskan pengaturan tentang pengawasan Otoritas Jasa Keuangan terhadap praktek fintech peer to peer lending dan menjelaskan pelaksanaan pengawasan Otoritas Jasa keuangan terhadap penyimpangan praktek fintech peer to peer lending yang merugikan konsumen jasa keuangan ditinjau hukum positif. Metode penelitian yang digunakan adalah yuridis normatif karena penelitian ini berdasarkan pendekatan peraturan perundang-undangan OJK yang berkaitan dengan fintech peer to peer lending dihubungkan pengawasan Otoritas Jasa Keuangan terhadap praktek fintech peer to peer lending yang merugikan konsumen jasa keuangan. Pengaturan tentang pengawasan OJK terhadap fintech peer to peer lending ini pertama kali di tahun 2016 yaitu POJK No.77/POJK.01/2016 tentang Layanan Pinjam Meminjam Berbasis Teknologi membahas penyelenggaraan mekanisme penyelenggaraan fintech peer to peer lending dan hanya mengawasi secara sub-sektoral saja, bentuk pengawasan ini adalah pengawasan eksternal. Terkait mengenai sanksi pada POJK No.77/POJK.01/2016 terdapat tidak ada kepastian hukum dan bisa menimbulkan sengketa di kemudian hari, ditahun 2018 OJK mengeluarkan peraturan POJK No.13/POJK.02/2018 tentang Inovasi Keuangan Digital sebagai bentuk pengawasan preventif. Pelaksanaan pengawasan OJK terhadap penyimpangan praktek fintech peer to peer lending yang merugikan konsumen jasa keuangan OJK membentuk Satuan Tugas Waspada Investasi untuk mengatasi beredarnya fintech-fintech ilegal namun masih belum maksimal karena keterbatasan kewenangan pada OJK. Saran penulis untuk OJK adalah mengatur lebih jelas dan spesifik mengenai pengawasan yang terdapat pada peraturan POJK No.77/POJK.01/2016 dan untuk Satgas Waspada Investasi meningkatkan sistem pendekteksi fintech peer to peer lending ilegal dan meningkatkan kualitas dalam pengawasan fintech peer to peer lending ilegal.